Bovine bile as a bio-surfactant pre-treatment option for anaerobic digestion of high-fat cattle slaughterhouse waste. Issue 1 (February 2018) - Harris, Peter W.; Schmidt, Thomas; McCabe, Bernadette K.
Highlights: Investigated bile pre-treatment on anaerobic digestion of high-fat abattoir waste. Bile dosed at 0.6 g/L improved SMP by 7.08%. Anaerobic toxicity assay of bile at 1–6 g/L found that bile has inhibitory effect. Bile dosed at 3–6 g/L decreased SMP by up to 6% in BMP tests. Bile at 0.2 g/L was found economically competitive to current pharmaceutical use. Abstract: Bovine bile was assessed as a novel bio-surfactant pre-treatment to enhance anaerobic digestion of lipid-rich dissolved air flotation (DAF) sludge using biochemical methane potential (BMP) tests. Bile was dosed at arbitrary concentrations from 0.2–6 g/L. At 0.6 g bile/L, methane yield increased by 7.08%. Doses above 2 g bile/L produced negative impacts on SMP, kinetics and digestion profile. At 6 g/L bile produced a 6% decrease in specific methane production and up to 79% additional inhibitory duration, delayed time of peak methane production by up to 74%, and slowed total digestion time by up to 65%. Reaction kinetics declined linearly with respect to bile addition, reaching half the control value at 6 g/L bile concentration. Subsequent anaerobic toxicity assays between 1 and 6 g bile/L revealed that bile has an inhibitory effect under BMP testing at these higher doses. The economic viability of using bile as a bio-surfactant was assessed. In comparison to the current use of bile as a sale product to pharmaceutical companies, the addition of 0.2 g bile/L to existing slaughterhouse waste streams could increase the value of bile to 220% of its current sale value. The promising results of bile dosed at 0.6 g/L under BMP testing warrant further investigation into long-term impact of bile pre-treatments of high-fat slaughterhouse wastewater in semi-continuous digestion experiments.